Pathology of Podocytopathies Causing Nephrotic Syndrome in Children - Ranganathan, Sarangarajan (Frontiers in Pediatrics, 2016)
Nephrotic syndrome (NS) in children includes a diverse group of diseases that range from genetic diseases without any immunological defects to causes that are primarily due to immunologic effects. Recent advances in molecular and genomic studies have resulted in a plethora of genetic defects that have been localized to the podocyte, the basic structure that is instrumental in normal filtration process. While the disease can manifest from birth and into adulthood, the primary focus of this review would be to describe the novel genes and pathology of primary podocyte defects that cause NS in children. This review will restrict itself to the pathology of congenital nephrotic syndrome, minimal change disease and its variants and focal segmental glomerulosclerosis. The two major types of congenital nephrotic syndrome are Finnish type characterized by dilated sausage shaped tubules morphologically and diffuse mesangial sclerosis characterized by glomerulosclerosis. Minimal change disease has usually normal appearing biopsy features on light microscopy and needs electron microscopy for diagnosis, while FSGS in contrast has classic segmental sclerosing lesions identified in different portions of the glomeruli as well as tubular atrophy. This review summarizes the pathologic characteristics of these conditions and also delves into the various genetic defects that have been described as the cause of these primary podocytopathies. Other secondary causes of NS in children such as membranoproliferative and membranous glomerulonephritis will not be covered in this review.